Optimalisation of Home Garden in Babakan Village Cisaat District Sukabumi Regency - Rahayu, Arifah (Universitas Djuanda, 2015)
Home garden has many functions, either for food production, children play ground or to conserve water, land and plant genetic resources.This programme aimed to improve the capability of women household in home garden management. especially to increase household income. The programme has succeeded to increase the use of home garden well, sustainable and fairly environment. Basides that the women household have produced many kind of vegetables and fruits. The interesting to apply the extension and training materials, and to continue the activities although the programme has finished.